Cervical ectopic pregnancy: a rare complication - Singh, Sanjay; Kumar, Amit; Dey, Madhusudan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Cervical ectopic gestation is a rare site and frequently confused with neoplastic process. Profuse bleeding can occur if the placenta is mistaken for a tumor and a biopsy is taken which may lead to hysterectomy. Cervical gestation also can be mistaken for an incomplete abortion where Products Of Conception (POC) are retained within the cervical canal may lead to diagnostic dilemma. We are presenting a case of cervical ectopic which was successfully managed conservatively.